2022
DOI: 10.1007/s00737-022-01229-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress during the prenatal period: assessing measurement invariance of the Perceived Stress Scale (PSS-10) across cultures and birth parity

Abstract: Maternal prenatal stress places a substantial burden on mother’s mental health. Expectant mothers in low- and middle-income countries (LMICs) have thus far received less attention than mothers in high-income settings. This is particularly problematic, as a range of triggers, such as exposure to traumatic events (e.g. natural disasters, previous pregnancy losses) and adverse life circumstances (e.g. poverty, community violence), put mothers at increased risk of experiencing prenatal stress. The ten-item Perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Sum scores range from 0-40. The PSS has demonstrated robust psychometric properties across a range of LMIC settings (Katus et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sum scores range from 0-40. The PSS has demonstrated robust psychometric properties across a range of LMIC settings (Katus et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…A number of foundational studies in LMICs have examined the rates and psychosocial predictors of perinatal depression (Atuhaire et al, 2020;Endomba et al, 2021;Roddy Mitchell et al, 2023), but the literature examining pregnancy anxiety (Bayrampour et al, 2016;Hadfield et al, 2022;Nath et al, 2019) and perceived stress (e.g., Katus et al, 2022) is still emergent. A number of poverty-related factors, including low income, household overcrowding, food insecurity, and gender inequality have consistently been found to predict elevated mood difficulties during pregnancy across cultural contexts in LMICs (Atif et al, 2015;Lund et al, 2010;McNab et al, 2022).…”
Section: Rights Retention Statementmentioning
confidence: 99%
“…Although we did not aim to test a longitudinal stress model, we thought it was important to examine whether maternal stress at 3 months was concurrently related to infant negative affect. Number of children in the home as an imperfect proxy for parity was also considered, as previous research has demonstrated links between parity and prenatal stress and infant emotional reactivity (Grant et al., 2010 ; Katus et al., 2022 ). Finally, prenatal anxious and depressive symptoms have been linked to prenatal stress and infant emotional problems (Brown et al., 2021 ; Davis et al., 2007 ), thus we included correlations with the State‐Trait Anxiety Inventory Trait sum score (Spielberger, 1983 ) and the PROMIS Depression Short Form T scores (Pilkonis et al., 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the large amount of research aimed at exploring the factorial structure of the PSS, there is still a limited number of studies that used item response theory (IRT) to understand the fit of the items and their differential functioning (Nielsen & Dammeyer, 2019;Reyna et al, 2019). Katus et al (2022) suggests that assessing the equivalence of measurements across settings is a vital first step toward extending the use of stress assessments in low and middle income countries. In this sense, several researchers claim that it is necessary to compare different groups on a latent construct like PSS-10 (Islam, 2020).…”
mentioning
confidence: 99%